Supra-auricular versus Sinusectomy Approaches for Preauricular Sinuses - El-Anwar,Mohammad Waheed (2016)
Abstract Introduction Several surgical techniques and modifications have been described to reduce the high recurrence rate after excision of preauricular sinus. Objectives The aim of this study is to review the literature regarding surgical approaches for preauricular sinus. Data Synthesis We performed searches in the LILACS, MEDLINE, SciELO, PubMed databases and Cochrane Library in September, 2015, and the key words used in the search were "preauricular sinus," "sinusectomy," "supra-auricular approach," "methylene blue," and/or "recurrence." We revised the results of 17 studies, including 1270 preauricular sinuses that were surgically excised by sinusectomy in 937 ears and by supra-auricular approach in 333 ears. Recurrence with supra-auricular was 4 (1.3%) while sinusectomy was 76 (8.1%) with significant difference (p< 0.0001). There were no reported facial nerve paresis or paralysis in any of the approaches. The sinusectomy approach showed significantly more complications (p= 0.0048). Conclusion Supra-auricular approach had significantly less recurrence rate than tract sinusectomy approaches. Thus, it could be regularly chosen as the standard procedure for preauricular sinus excision. As such, it would be helpful for surgeons to be familiar with this approach.